Lactate Clearance as an Early Prognostic Marker of Mortality for Pediatric Trauma - Çeleğen, Mehmet; Çeleğen, Kübra (Klinische Pädiatrie, 2022)
Background While lactate clearance (LC) has already been shown as a prognostic indicator in clinical studies, its certain character needs to be defined in pediatric trauma. This research aimed to evaluate the correlation between early lactate clearance and mortality in pediatric trauma.Patients and methods A retrospective cohort study was conducted in a university hospital. Repeated LC was measured at admission, at the 2nd, 6th, and 12th hours post-admission. The association of lactate clearance with mortality was analyzed and using receiver operating characteristic (ROC) to determine the threshold levels of lactate clearance and also logistic regression analysis was performed to determine whether LC was an independent risk factor.Results Seventy-eight patients were included and overall mortality was 13%. LC values of the non-survivors was significantly lower than survivors for LC0–2 h (28.60±14.26 vs 4.64±15.90), LC0–6 h (46.63±15.23 vs 3.33±18.07), LC0–12 h (56.97±15.53 vs 4.82±22.59) (p:<0.001, p:<0.001 and p:<0.001, respectively). Areas under the curve of lactate clearance at the 2nd, 6th, and 12th hours after therapy start were a significant predictor for mortality (p:<0.001, p:<0.001, and p:<0.001, respectively). Threshold values of LC were 12.9, 19.5 and 29.3%, respectively.Conclusion Lactate clearance was a beneficial tool to estimate outcomes of pediatric trauma. Poor lactate clearance was a significant marker for poor prognosis.
Keywords: Lactate; Lactate clearance; Pediatric; Trauma; Mortality